FINANCIAL PERFORMANCE ANALYSIS AT PT. INDOSAT TBK. PERIOD 2017 – 2021 CENTRAL JAKARTA - Irene Vincentia Rudi; Habiburrahman (ZILLZELL MEDIA PRIMA, 2024)
PT. Indosat Tbk. is a telecommunications service provider company in Indonesia. This research aims to determine the financial performance of PT. Indosat Tbk. using financial ratio analysis, namely liquidity ratios, solvency ratios and profitability ratios. The research data collection technique comes from the annual financial report of the company PT. Indosat Tbk. 2017-2021 listed in Issuer Performance. This research was carried out using qualitative methods. Data analysis and discussion uses a comparative analysis method with a descriptive approach. This research analysis tool uses liquidity, solvency and profitability ratios which include current ratio, quick ratio, debt to assets ratio, debt to equity ratio, rate of return on investment, net profit margin, return on equity and earnings per share of common stock. The results of this research show that the liquidity ratio analysis of PT. Indosat Tbk. on financial performance during 2017-2021 as measured by the current ratio and quick ratio is considered very bad, because the increase in current debt is greater than the increase in current assets. Analysis of PT's solvency ratio. Indosat Tbk. The financial performance during the 2017-2021 period as measured by DAR and DER is considered very bad, because the company's funding is mostly funded by debt originating from creditors. Analysis of profitability ratios of PT. Indosat Tbk. on financial performance during 2017-2021 as measured by the rate of return on investment, net profit margin, return on equity and earnings per share of common stock is considered not very good, because the company management does not manage the company's operations optimally. The author states that PT. Indosat Tbk. Measuring financial performance using ratio analysis results in the overall ratio calculation being that current liabilities are greater than current assets.